Impact of nanosizing a host matrix based on a metal–organic framework on solid-state fluorescence emission and energy transfer. Issue 4 (14th January 2022) - Sakamoto, Hikaru; Ito, Akitaka; Ohtani, Masataka
Abstract : We demonstrate that the nanosize effect of a host matrix appears to affect the emission properties of guest dye molecules encapsulated in the pores of a metal–organic framework as a host (dye@MOF). Abstract : We demonstrate that the nanosize effect appears to affect the properties of dye molecules encapsulated in the pores of a metal–organic framework (dye@MOF). The emissive properties of the nanosized dye@MOF are improved compared with those of sub-micron-sized dye@MOF. The fluorescence energy transfer between encapsulated dye molecules and adsorbed quencher molecules exhibits a higher efficiency with a smaller dye@MOF crystal compared with a larger dye@MOF crystal.